Who Lends Before Banking Crises? Evidence from the International Syndicated Loan Market - Giannetti, Mariassunta; Jang, YeeJin (Management Science, 2025)
Existing studies assume that all lenders have similar incentives to take on risks during different phases of the lending cycle. We show that foreign lenders and low market share lenders extend more credit in comparison with other lenders during lending booms leading to banking crises but not during other credit expansions. These less established lenders also shorten loan maturity and increase the amount of credit they extend to riskier borrowers without asking for collateral or imposing covenants and higher interest rates. Our results suggest that foreign lenders and low market share lenders contribute disproportionately to credit misallocation and risk accumulation in precrisis periods. This paper was accepted by Victoria Ivashina, finance. Funding: M. Giannetti acknowledges financial support from the Bank of Sweden Tercentenary Foundation [P16-0328] and Jan Wallanders och Tom Hedelius stiftelse [P20-0127]. Supplemental Material: The internet appendix and data files are available at https://doi.org/10.1287/mnsc.2022.03505 .